La revocación del reconocimiento de estatalidad en el Derecho Internacional - Rosales Zamora, Pablo (2023)
While there are extensive doctrinal reflections on the study of States in international law, there has been little interest in the analysis of the revocation of statehood recognition (derecognition) and its legal feasibility. Some scholars have argued that this is because such a phenomenon is purely theoretical and rarely observed in reality.Considering that there are prominent cases where the revocation of previously granted statehood recognition is evident, the most frequent being those of some “emerging states”, it is considered that the withdrawal of recognition deserves to be examined and criticized from the perspective of public international law; moreover, because the doctrine is a tool that can assist states in the examination of specific cases involving derecognition. States need to have guidelines that allow them to orient themselves in relation to the revocation of recognition and to know whether there are scenarios where it is considered possible to use this figure.In this sense, the authors aim to explore some of the probable contexts surrounding the revocation of recognition of statehood, offering a vision of this figure from the principle of good faith in public international law. Additionally, they propose a formula for the exceptional application of withdrawal of recognition in the context of premature recognition or the loss of some of the elements of statehood.